Reading Rahab with Larsen towards a New Direction in African American Biblical Hermeneutics - Russaw, Kimberly D. (2020)
This article explores what it might look like to read the biblical story of Rahab alongside literature from the African American literary canon. Specifically, the article examines the biblical account of Rahab found in Joshua 2 through the lens of identity and argues that, like characters in Harlem Renaissance author Nella Larsen’s novels Quicksand and Passing, Rahab is passing in Joshua 2. The characters Helga Crane from the novel Quicksand and Clare Kendry from the novel Passing serve as exemplars for passing (the act of presenting as of a different racial group than one’s own), and the markers of passing are mapped on to Rahab. This article is a womanist work, as it seeks to center the experiences of Black women.
Keywords: African American; Nella Larsen; Rahab; passing; Prostitute; Womanist